KEMAMPUAN MENULIS TEKS PUISI BERDASARKAN OBJEK LANGSUNG SISWA KELAS X SMA MASMUR OLAHRAGA PEKANBARU - Afriyani, Lisa; Burhanudin, Dudung; Rumadi, Hadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This study discusses how the ability to write kuatrin the suitability aspect theme, diction and rhyme with the object of class X High School Masmur Sport Pekanbaru. This study aims to (1) Determine the ability to write kuatrin the suitability aspect theme, diction and rhyme with the object. The population in this study were all students of class X High School Masmur Sports Pekanbaru academic year 2013/2014, amounting to 25 people. This is a form of descriptive research is a method that examines the phenomenon under study or a portrait of what it is in accordance with what seemed at the time this study was conducted. Sources of data in this study consisted of poetry kuatrin aspects of the theme, diction and rhyme. Data collection techniques using test technique, which tests writing poetry text. Kuatrin new form of poetry consisting of four lines in each stanza rhyme aa-aa, ab-ab, aa-bb. The stages in the writing of poetry kuatrin are: (1) Students observe the school environment (2) Students write poetry texts based on observations of the school environment. Thus, the text written poems based on his interpretation of the school environment. While the analysis of the data using a method to measure the ability of each student is to provide a score that is adapted to the method of analysis, ie by giving value to the aspect of themes, diction, and rhyme. Based on the results of this study concluded that: (1) the results of these studies demonstrate the ability to write poetry kuatrin class X High School Masmur Sports Pekanbaru being categorized. This is evident from the data obtained. And the lack of interest of students to be interested in writing poetry.Keywords : poetry, kuatrin